Comments on previous psychological Tai-Chi models: Jun-zi self-cultivation model - Xu, Jin; Chang, Nam-Sat; Hsu, Ya-Fen; Shiah, Yung-Jong (Frontiers in Psychology, 2022)
In this article we describe four previous Tai-Chi models based on the I-Ching (Book of Changes) and their limitations. The I-Ching, the most important ancient source of information on traditional Chinese culture and cosmology, provides the metaphysical foundation for this culture, especially Confucian ethics and Taoist morality. To overcome the limitations of the four previous Tai-Chi models, we transform I-Ching cultural system into a psychological theory by applying Hwang’s (2018) epistemological strategy. Specifically, we propose the Jun-zi (君子) Self-Cultivation Model (JSM), which argues that an individual (小人, xiao-ren) can become an ideal person, or jun-zi, through the process of self-cultivation, leading to good fortune and the avoidance of disasters (趨吉避凶, qu-ji bi-xiong). The state of jun-zi is that of the well-functioning self, characterized by achieving one’s full potential and an authentic, durable sense of well-being. In addition, we compare egoism (xiao-ren) and jun-zi as modes of psychological functioning. The JSM can be used to as a framework to explain social behavior, improve mental health, and develop culturally sensitive psychotherapies in Confucian culture. Finally, an examination of possible theoretical directions, clinical applications, and future research is provided.